A qualitative assessment of disability friendly water and sanitation facilities in primary schools, Rumphi, Malawi. Issue 6 (2nd November 2018) - Zaunda, Harlod; H. Holm, Rochelle; Itimu-Phiri, Ambumulire; Malota, Mphatso; White, Sian
ABSTRACT: Students with disabilities commonly face barriers when accessing water and using sanitation and hygiene facilities at school. International frameworks have prompted governments to enact local policies that enshrine these rights, guarantee equitable access to education and mandate inclusive infrastructure. This research was designed to explore whether Malawi has translated good policies into practice. Data were gathered in Rumphi district, Malawi, through structured field observations in ten schools and interviews with students with a disability ( n  = 23), teachers ( n  = 11) and government stakeholders ( n  = 2). No school had facilities that fully meet the needs of students with disabilities, and private schools were not necessarily better. The cost of bringing existing infrastructure up to standard was on average MK54 000 (US$78). However, proactive consultation with children with a disability is likely to generate alternative low-cost short-term solutions. Increased government support, budgeting and enforcement is necessary to ensure international standards and national policies are met.